Música em cena: á escuta do documentário brasileiro - Cristiane da Silveira Lima (2015)
In a context where music has become the subject of renewed interest in Cinema and Communication research and Brazillian documentary cinema in particular, we seek to answer the following question: how does music, in Brazilian documentary film (in conjunction with imagesand sound), contribute to cinematic writing to engage the spectators listening? From the analysis of a large sampling of films that have chosen to use music in scene, we delve into two aspects:first, observation of the relationship between music, the other auditory elements (voice, noise and silence) and the visuals in the writing of the film; second, the pinpointing of how these articulations engage the complex, divided tasks of spectators listening. These analyses bring out new issues related to sound and listening in cinema, eliciting multiple forms of documentary film to establish affinity plastic, procedural or formal with the phenomenon of music.